P91 Trypsin-like protease activity predicts disease severity and patient mortality in adults with cystic fibrosis. (15th November 2016) - Reihill, JA; Moffitt, KL; Jones, AM; Elborn, JS; Martin, SL
Abstract : Introduction: Serine trypsin-like (TL) proteases, which are excessively active in CF airways, promote activation of the epithelial sodium channel (ENaC) and airways dehydration; a key initiating factor for CF lung disease pathogenesis. Furthermore TL-proteases enhance mucin gene expression and mucus hypersecretion, yet whether there is any relationship between the activity of these enzymes and CF pulmonary disease is unknown. Objectives: The primary objective of the current investigation was to determine whether TL-protease activity, measured in adult CF sputum sol, correlates with lung disease and patient outcome (survival). A secondary objective was to compare the strength of any relationships observed with that of neutrophil elastase (NE), an established protease biomarker. Methods: In this cross sectional retrospective study we analysed CF sputum sol collected from 30 clinically stable adult CF patients. Protease activity was measured by monitoring the hydrolysis of peptide-based substrates. Biomarkers of inflammation (IL-8 and TNF-α) were measured by ELISA. Lung function was assessed by spirometry (FEV1). Mortality data was retrospectively obtained and time in months until death or transplantation used for subsequent survival analysis. Results: TL-protease activity inversely correlated with lung function (FEV1) (r = −0.4, p = 0.031) however, no relationship with IL-8 and TNFα was observed. In contrast, NE was found to correlate with IL-8: r = 0.7, p < 0.001 and TNFα: r = 0.7, p < 0.001 but showed no relationship with lung function, indicating that these serine proteases play very distinct roles within the disease process. Kaplan-Meier analysis demonstrated significantly reduced survival for those individuals with above median TL-protease activity. Levels of NE activity showed no relationship with patient survival. Using a multivariate Cox regression analysis (adjusted for age and BMI) a significantly increased mortality hazard (HR 1.028, 95% CI: 1.007–1.049; p = 0.009) was also identified. These findings are supported by analysis of a validation cohort consisting of samples collected from a separate cohort of 33 adult CF patients. Conclusions: TL-protease activity inversely correlates with lung function and patient survival. As such tryptic activity may warrant consideration when modelling CF survivorship and should be investigated further as a biomarker of CF lung disease and as a potential therapeutic target.